Quantitative risk assessment for debris flows based on dynamic process: A case study of Huangniba gully, Muli County, Liangshan Prefecture, Sichuan Province - Dongpo WANG; Qi DONG; Liangbo LIAO; Shuai LU; Shuaixing YAN (地质科技通报)
Objective, Methods This study focus on debris flows in Huangniba gully, Muli County, Liangshan Prefecture, Sichuan Province, utilizing a mass flow numerical simulation platform. Through field investigations and the construction of numerical models, we analyze the mechanisms driving debris flow formation and evolution, aiming to invert these mechanisms.Based on this foundation, we assess debris flow hazards, develop a vulnerability model for masonry structures under different damage modes, and establish a dynamic process-based debris flow risk assessment method. Results The risk assessment indicates that, for a 20-year return period, very high- and high-risk zones for debris flow encompass 0.15×104 m2 and 1.68×104 m2, affecting 10 and 13 buildings, respectively. For a 50-year return period, the areas of very high- and high-risk zones expand by 40% and 70.8%, with 2 and 4 additional buildings affected. Moreover, for a 100-year return period, these zones increase by 113.3% and 132.1%, respectively, affecting 11 and 5 more buildings compared to the 20-year scenario. Conclusion Furthermore, the erosion-incorporating debris flow dynamics model developed in this study accurately represents the debris flow events in Huangniba gully. Additionally, the vulnerability assessment model for masonry structures was validated against other debris flow events, confirming its enhanced feasibility. These findings provide a foundation for quantitative risk prediction in Huangniba gully.